Faszyzacja antyfaszyzmu. Kulturowe kody wojny Rosji - Getka, Joanna; Darczewska, Jolanta (University of Warsaw Press, 2025)
This book, which builds upon our previous volume "Rus’ Abducted? Russia’s War over the Identity of Ukraine", offers a clear explanation of complex mechanisms of Russia’s war against the West, along with its methods used in both the virtual and physical spaces. The book also lays bare the mechanism of power in Russia, especially her constant eagerness to provoke armed conflicts and wars. This longue durée process requires a continuous renewal and adjustment of stereotypical confrontation scenarios, which results in collisions of meanings, associated as these are with the imperialist symbolic order being bent to fit the moment’s needs.